Marginal sealing property of temporary restorative materials a comparative study - Padua, Ana Rose (The Journal of the Philippine Dental Association)
This study aims to compare the marginal sealing property Provifil (Promedica, Germany), a new light-cured one-component temporary filling material with IRM (Dentsply-Caulk) and Cavit (3M ESPE).